Alcohol: another risk factor for diabetic retinopathy?. Issue 6423 (7th April 1984) - Young, R J; McCulloch, D K; Prescott, R J; Clarke, B F
Abstract : In a five year prospective study clinical features associated with the development and progress of retinopathy were sought in 296 randomly selected diabetic men aged 20-59. None had ophthalmoscopically detectable retinopathy initially, but during follow up 66 developed the condition (47 background, 10 exudative, 9 proliferative). Linear logistic analyses (two tailed tests) showed that the initial features independently predictive of retinopathy were duration of diabetes, poor glycaemic control, impotence, and--unexpectedly--heavy alcohol consumption. Poor glycaemic control in the interim and proteinuria at review were also associated with the development of retinopathy. No relation was found with smoking or obesity. Glycaemic control and alcohol consumption were therefore the only aetiologically relevant associations identified. The development of severe retinopathy (exudative and proliferative) showed a particular association with heavy alcohol consumption, occurring in nine of the 70 heavy drinkers (13%) compared with 10 (4.4%) of the rest. Alcohol consumption may be an important independent factor associated predictively with sight threatening diabetic retinopathy.